The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13018-020-1548-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of wear performance in femoral and tibial conformity in patient-specific cruciate-retaining total knee arthroplasty

Abstract: Background: Articular surface curvature design is important in tibiofemoral kinematics and the contact mechanics of total knee arthroplasty (TKA). Thus far, the effects of articular surface curvature have not been adequately discussed with respect to conforming, nonconforming, and medial pivot designs in patient-specific TKA. Therefore, this study evaluates the underlying relationship between the articular surface curvature geometry and the wear performance in patient-specific TKA. Methods: We compare the wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…This trend was also found in CR patient-specific TKA [100]. A previous study showed that conformity changes in the femoral and tibial inserts influence the wear performance in CR patient-specific TKA [100].…”
Section: Discussion and Future Directionsupporting
confidence: 70%
See 3 more Smart Citations
“…This trend was also found in CR patient-specific TKA [100]. A previous study showed that conformity changes in the femoral and tibial inserts influence the wear performance in CR patient-specific TKA [100].…”
Section: Discussion and Future Directionsupporting
confidence: 70%
“…This trend was also found in CR patient-specific TKA [100]. A previous study showed that conformity changes in the femoral and tibial inserts influence the wear performance in CR patient-specific TKA [100]. Kinematics and contact parameters should be considered to improve wear performance in CR patient-specific TKA [100].…”
Section: Discussion and Future Directionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies have shown that component alignment affects the kinematics of the knee joint, including the femoral anteroposterior translation and tibial rotation ( Shih et al, 2020 ; Wang et al, 2021 ; Fang et al, 2022 ). Malignment can also produce higher stress and contact pressure on the tibial insert, which may increase wear and lead to premature failure ( Rostoker and Galante, 1979 ; Liau et al, 1999 ; Liau et al, 2002 ; Cheng et al, 2003 ; Koh et al, 2020 ). Therefore, it is not sufficient to only assess the standard alignment position during pre-clinical testing, various alignments based on clinical feedback should be evaluated, with consideration also given to increasing the alignment tolerance.…”
Section: Introductionmentioning
confidence: 99%